NATIONAL LAW DEVELOPMENT AS IMPLEMENTATION OF PANCASILA LAW IDEALS AND SOCIAL CHANGE DEMANDS - Achmad Irwan Hamzani; M Mukhidin (Jurnal Dinamika Hukum, 2018)
Social life changes over time. The response to social change and law change is all important. The ideal national law system  Indonesian people expect is Pancasila law system. The problem in this research is First, what is the description of the Pancasila law ideals? Second, why development of national law as implementation of Pancasila law ideals is important? and Third, is national law development also the social change demands? This research employs normative approach which constitutes secondary data in the form of library materials. The analysis applied induction-interpretation-conceptualization. The results show that Pancasila law ideals is an expectation of a law system rooted in Pancasila which is a way of life of the Indonesian nation. The development of national law system is an attempt to establish its own product laws. The importance of national law development is to manifest the Pancasila law ideals. The law development in the context of social change is to meet social change. The national law development will be more effective if initiated from the substance of law.Keywords: Development, national law, ideals of law, Pancasila, social change.